2015
DOI: 10.1155/2015/214836
|View full text |Cite
|
Sign up to set email alerts
|

EGCG Attenuates Uric Acid-Induced Inflammatory and Oxidative Stress Responses by Medicating the NOTCH Pathway

Abstract: Background. The aim of this study is to investigate whether (-)-epigallocatechin-3-gallate (EGCG) can prevent the UA-induced inflammatory effect of human umbilical vein endothelial cells (HUVEC) and the involved mechanisms in vitro. Methods. HUVEC were subjected to uric acid (UA) with or without EGCG treatment. RT-PCR and western blots were performed to determine the level of inflammation marker. The antioxidant activity was evaluated by measuring scavenged reactive oxygen species (ROS). Functional studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…As described in previous studies [31, 32], the statistical analysis was performed with the Statistical Package for Social Sciences (SPSS version 13.0; IBM Analytics, Chicago, IL, USA). All the data were expressed as mean ± SD (standard deviation, SD) and the difference was analyzed by a one-way ANOVA test.…”
Section: Methodsmentioning
confidence: 99%
“…As described in previous studies [31, 32], the statistical analysis was performed with the Statistical Package for Social Sciences (SPSS version 13.0; IBM Analytics, Chicago, IL, USA). All the data were expressed as mean ± SD (standard deviation, SD) and the difference was analyzed by a one-way ANOVA test.…”
Section: Methodsmentioning
confidence: 99%
“…Notch signaling pathway is an evolutionarily conserved signaling pathway that controls the fate of cells and maintenance of stemness [37]. EGCG could inhibit Notch signaling pathway [22][23][24]38], Especially, it was found that Notch signaling pathway inactivation can effectively reduce cisplatin induced osteosarcoma stem cells production and reduce the resistance of osteosarcoma cells [39], which suggested that Notch signaling pathway play a role in OS drug resistance and stemness. In our research, by detecting downstream target genes of Notch signaling (Hes1 and Hey1), it was proved that V7 overexpression could further activated Notch signaling and EGCG treatment could inhibit the Notch signaling pathway in OSCs.…”
Section: Disscussionmentioning
confidence: 99%
“…The possible mechanisms by which SUA accelerated arterial stiffness have been proposed as follows. First, uric acid stimulates inflammatory pathways by nuclear factor-κB, Notch-1, and chemoattractant protein 1 signals [26,27]. Second, uric acid increases production of reactive oxygen species and decreases the bioavailability of nitric oxide in vascular endothelial cells and induces endothelial dysfunction [27,28].…”
Section: Discussionmentioning
confidence: 99%